Harbinger - Spencer, Wen (Spencer, Wen. Elfhome series, 2023)
"The war against the oni heats to a flashpoint even as Tinker learns that the enemy has a dangerous new weapon, the nactka. What's more, the Stone Clan has sent its most famous warlords, the Harbingers, to take control of the allied war effort. Are these elves friends or foes? Tinker's newfound baby siblings are up for grabs. The babies, though, are wood sprites and aren't going to take things lying down. Team Mischief go!"--